Antecedents and Consequences of Destination Brand Attachment: Empirical Study on Surya Waterboom - Rahmayanti, Nynda (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
—Surya Waterboom as a tourist destination faces competition among its competitors. Todistinguish one tourist destination from another, Surya Waterboom needs a brand as the identity of atourist destination. This study aims to determine the antecedents and consequences of destination brandattachment to the Surya Waterboom tourist destination. The sample in this study was conducted using theSlovin formula as many as 100 respondents. The sampling technique used was purposive sampling. Datawere obtained using a questionnaire measured by a Likert scale. This study uses Partial Least Squareregression analysis using SmartPLS 3.0 software to process the data. The results showed that memorabletourist experiences had a significant effect on destination brand attachments, memorable touristexperiences did not have a significant effect on the intention to visit destinations, perceived quality had asignificant effect on destination brand attachments, and destination brand attachments had a significanteffect on the intention to revisit a destination